Energy Depletion and Stress Levels in Sockeye Salmon Migrating at the Northern Edge of their Distribution. Issue 4 (3rd June 2019) - Carey, Michael P.; Keith, Kevin D.; Schelske, Merlyn; Lean, Charlie; McCormick, Stephen D.; Regish, Amy; Zimmerman, Christian E.
Abstract: The physiological challenge for anadromous fish to migrate upriver is influenced by river temperature, but the impacts of river temperature can be difficult to predict due to an incomplete understanding of how temperature influences migration costs, especially in high‐latitude (>60°N) ecosystems. To assess temperature influences on migrating Pacific salmon Oncorhynchus spp., we measured heat shock protein 70 (HSP70), as an indicator of cellular stress, and energy content of Sockeye Salmon Oncorhynchus nerka throughout their upriver migration in the Pilgrim River, Alaska. Although HSP70 was elevated as fish moved to the spawning grounds and was higher in fish with low energy content, HSP70 did not increase with warmer river temperatures. We verified in an experiment that HSP70 abundance in Sockeye Salmon does respond to temperatures above 20.5°C. Over the 4 years of sampling, energy content decreased at similar rates as Sockeye Salmon moved upstream. We expected Sockeye Salmon energy levels would be lower when migrating in warmer river temperatures; however, we found higher energy levels occurred with higher temperatures in the Pilgrim River. We hypothesize that the relationship between temperature and energy content is due to river temperatures often occurring below optimal temperatures for migration. Lower temperatures could be energetically costly or reduce migration rates, both of which would result in lower energy content with cooler temperature. Understanding interactions between environmental drivers and physiological responses will help managers anticipate future changes for Sockeye Salmon at the northern edge of their distribution.